Johanna's bridegroom ebook - Miller, Emma (Hannah's Daughters., 2013)
Will You Marry Me? Bold widow Johanna Yoder stuns Roland Byler when she asks him to be her husband. To Johanna, it seems very sensible that they marry. She has two children, and he has a son. Why shouldn't their families become one? But the widower has never forgotten his long-ago love for her; it was his foolish mistake that split them apart. This could be a fresh start for both of them. Until she reveals she wants a marriage of convenience only. It's up to Roland to woo the stubborn Johanna and convince her to accept him as her groom in her home and in her heart.